Фінансово-економічна криза та її вплив на формування регіональної політики розвитку банківської системи України - Копилюк, О.І. (Економіка промисловості, 2014)
Досліджено вплив фінансової кризи на діяльність банків в Україні. Представлено основні негативні чинники, які дестабілізують роботу банків на національному та регіональному рівнях, що призвело до збитків. Запропоновано напрями вдосконалення розвитку регіональних банківських систем, розробки регіональної політики розвитку банківського сектору економіки. Исследовано влияние финансового кризиса на деятельность банков в Украине. Представлены основные негативные факторы, дестабилизирующие работу банков на национальном и региональном уровнях, что привело к убыткам. Предложены направления совершенствования развития региональных банковских систем, разработки региональной политики развития банковского сектора экономики. The effect of the financial crisis on banks in Ukraine and singled out factors, such as the gap between basic indicators in the domestic banking over a long time (the discrepancy between the terms of funding and allocation of resources by banks), significant "dollarization" of the given credits, significant amount of foreign currency consumer credits and inadequate personal income of individuals, inadequate capitalization of banks, non-compliance of certain regulations with the requirements of increasing the operational, financial and investment risks of banks, destabilized banks at national and regional levels, and resulted in losses. The analysis and evaluation of the efficiency of the regional banking system of Ukraine revealed the asymmetries and imbalances of its development and suggested the division into regions of high, medium and low concentration of institutions and capital. It is proved that the major problem of the banking system of Ukraine is its territorial unevenness accompanied by a high concentration of institutions and their capital within a region, especially in Kiev, where the concentration of capital is the largest. Directions of improvement of regional banking systems are as follows: analyzing and reforming the existing legal framework, developing recommendations for socio-economic and cultural development of the regions by means of distinguishing mechanisms of attracting potential banking institutions to the development of local communities and identification of priority areas to fund and allocate financial resources, meet the various development needs at the level of areas, study tools of effectively functioning regional banking systems and the development of regional policy for the banking sector, which is the strategy and tactics of forming and effective functioning of banking institutions of regions that interact with each other and with the environment, carry out resource support for economic, social, labor, political, legal and other relationships and satisfying innovation and investment needs of the regional economy.